When targets strike back: how negative workplace gossip triggers political acts by employees - Cheng, Bao; Dong, Yun; Zhang, Zhenduo; Shaalan, Ahmed; Guo, Gongxing; Peng, Yan (Springer, 2020)
This study examines why and when negative workplace gossip promotes self-serving behaviors by the employees being targeted. Using conservation of resources (COR) theory, we find that targets tend to increase their political acts as a result of ego depletion triggered by negative gossip. We also show that sensitivity to interpersonal mistreatment and moral disengagement moderate this process. Specifically, we demonstrate that targets with high levels of sensitivity to interpersonal mistreatment are more likely to experience ego depletion, and that targets with high levels of moral disengagement will find it easier to persuade themselves to engage in political acts. We conducted a three-wave time-lagged survey of 265 employees in Guangdong, China, to test our hypotheses. The results support our theoretical model and indicate that COR theory can be used to explain the impacts of negative workplace gossip. Alongside our important and timely theoretical contributions, we provide new perspectives on how managers can avoid or mitigate these political acts.
Keywords: negative workplace gossip; political acts; moral disengagement